2008
DOI: 10.1073/pnas.0708452105
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model for LRRK2 -linked parkinsonism

Abstract: Mutations in the leucine-rich repeat kinase (LRRK2) gene cause lateonset autosomal dominant Parkinson's disease (PD) with pleiomorphic pathology. Previously, we and others found that expression of mutant LRRK2 causes neuronal degeneration in cell culture. Here we used the GAL4/UAS system to generate transgenic Drosophila expressing either wild-type human LRRK2 or LRRK2-G2019S, the most common mutation associated with PD. Expression of either wild-type human LRRK2 or LRRK2-G2019S in the photoreceptor cells caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
248
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(272 citation statements)
references
References 37 publications
20
248
1
Order By: Relevance
“…Interestingly, Tg flies expressing either human WT or mutant G2019S LRRK2 exhibit selective loss of DA neurons, locomotor dysfunction, and early mortality (19), whereas Tg expression of WT or pathogenic equivalent mutant forms of LRRK, the sole Drosophila ortholog of human LRRK2, does not result in any significant defects in flies (18). However, it is unclear why expression of human LRRK2 or fly LRRK has such different effects in flies, and why expression of either WT or mutant human LRRK2 similarly results in loss of DA neurons in flies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Tg flies expressing either human WT or mutant G2019S LRRK2 exhibit selective loss of DA neurons, locomotor dysfunction, and early mortality (19), whereas Tg expression of WT or pathogenic equivalent mutant forms of LRRK, the sole Drosophila ortholog of human LRRK2, does not result in any significant defects in flies (18). However, it is unclear why expression of human LRRK2 or fly LRRK has such different effects in flies, and why expression of either WT or mutant human LRRK2 similarly results in loss of DA neurons in flies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee et al (18) reported that loss-of-function mutants for LRRK, the sole Drosophila ortholog of human LRRK2, exhibited severely impaired locomotor activity and reduced tyrosine hydroxylase (TH) immunoreactivity in DA neurons, but transgenic (Tg) expression of pathogenic mutant or WT LRRK did not result in any significant defects. However, in another study, Tg expression of human WT or G2019S LRRK2 led to adult-onset selective loss of DA neurons, locomotor dysfunction, and early mortality in Drosophila (19).…”
mentioning
confidence: 94%
“…Transgenic expression of human G2019S LRRK2 in Drosophila causes dendrite degeneration and dopaminergic (DA) neurons loss followed by locomotor dysfunction [114,115]. Importantly, this effect was diminished by pharmacological inhibition of kinase activity of G2019S mutant or by overexpression of parkin, a protein implicated in autosomalrecessive Parkinsonism [116,117].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…Overexpression of dLRRKWT or Roc domain substitution R1069C (comparable to Lrrk2 R1441C in humans) using a number of different GAL4 drivers (directed to muscle, whole-body and dopaminergic neurons) produced no deleterious effects [75]. The effects of overexpression of human WT and G2019S Lrrk2 were investigated using GAL4 drivers for the photoreceptor cells (gmr-GAL4) or in dopaminergic neurons (ddc-GAL4) [77]. Progressive retinal degeneration was observed in gmr-GAL4 WT and G2019S flies similar to that shown in other fly neurodegeneration models.…”
Section: Fly Modelsmentioning
confidence: 99%